2022
DOI: 10.1038/s41598-022-25271-6
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of the methanolic leaf extract of Prosopis laevigata

Abstract: The appearance of antimicrobial-resistant pathogens has highlighted the need to search for new compounds that can effectively combat infectious diseases. A potential source of these compounds are the secondary metabolites of species that have been reported as effective traditional treatments of such diseases. Prosopis laevigata is a medicinal plant, and its chemical constituents have shown potential antimicrobial activity. In this study, the antimicrobial activities of the methanolic extract of the leaves of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…Thus, the findings of this study were in close agreement with those reported for the antimicrobial activity of stigmasterol and β-sitosterol from the roots of C. populnea [17] and β-sitosterol from the leaves of the plant, C. populnea [8]. Even though there is limited information on the mechanism of antimicrobial activity of stigmasterol and β-sitosterol, some studies have shown that the compounds have a broad spectrum of antibacterial and antifungal properties [30,31]. Stigmasterol has been reported to inhibit the growth of C. albicans, viruses and tropicalis at low concentrations [32].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Thus, the findings of this study were in close agreement with those reported for the antimicrobial activity of stigmasterol and β-sitosterol from the roots of C. populnea [17] and β-sitosterol from the leaves of the plant, C. populnea [8]. Even though there is limited information on the mechanism of antimicrobial activity of stigmasterol and β-sitosterol, some studies have shown that the compounds have a broad spectrum of antibacterial and antifungal properties [30,31]. Stigmasterol has been reported to inhibit the growth of C. albicans, viruses and tropicalis at low concentrations [32].…”
Section: Discussionsupporting
confidence: 90%
“…Antimicrobial activity of C4C5 was determined using agar well diffusion method as described by Yusuf et al [30]. A quantity (0.001 mg) of C4C5 was weighed and dissolved in 10 cm 3 of DMSO to obtain a concentration of 100 µg/cm 3 each.…”
Section: Susceptibility Testmentioning
confidence: 99%
See 2 more Smart Citations
“…The method described by Jensen et al [19,20] was adopted with minor modifications. Into sterile test tubes was placed 1 mL of nutrient broth.…”
Section: Minimum Inhibitory Concentration Assay (Mic)mentioning
confidence: 99%